Case based rubella surveillance in Abia State, South East Nigeria, 2007–2011 - Chukwuemeka Anthony Umeh; Stella Chioma Onyi (PeerJ, 2014)
Introduction. Rubella infection has the potential of causing severe fetal birth defects collectively called congenital rubella syndrome (CRS) if the mother is infected early in pregnancy. However, little is known about rubella and CRS epidemiology in Nigeria and rubella vaccines are still not part of routine childhood immunization in Nigeria.Methods. Analysis of confirmed cases of rubella in Abia State, Nigeria from 2007 to 2011 detected through Abia State Integrated Disease Surveillance and Response system.Results. Of the 757 febrile rash cases, 81(10.7%) tested positive for rubella immunoglobulin M (IgM). New rubella infection decreased from 6.81/1,000,000 population in 2007 to 2.28/1,000,000 in 2009 and increased to 6.34/1,000,000 in 2011. The relative risk of rubella was 1.5 (CI [0.98–2.28]) times as high in females compared to males and 1.6 times (CI [0.90–2.91]) as high in rural areas compared to urban areas. Eighty six percent of rubella infections occurred in children less than 15 years with a high proportion of cases occurring between 5 and 14 years.Conclusion. Rubella infection in Abia State, Nigeria is predominantly in those who are younger than 15 years old. It is also more prevalent in females and in those living in rural areas of the state. Unfortunately, there is no surveillance of CRS in Nigeria and so the public health impact of rubella infection in the state is not known. Efforts should be made to expand the rubella surveillance in Nigeria to incorporate surveillance for CRS.